Automated Water Heating Management with Internet of Things - Hera Susanti; Afrizal Abdi Musyafiq; Hendi Purnata; Novita Asma Ilahi; Saepul Rahmat (Politeknik Negeri Malang, 2023)
IoT devices can range from smart home devices such as thermostats and security systems to industrial control systems used in manufacturing and other industries. One focus of the IoT-based monitoring and control concept is monitoring and controlling water heaters based on IoT technology to support the creation of a smart home. The purpose of this research is to create a system that can control and monitor water heaters remotely using the Android Studio application so that the water temperature in the heater can be ensured for safety, comfort, reliability, and energy efficiency. The system is designed using temperature sensors and water flow sensors, and then the data is processed with the NodeMCU microcontroller and then sent to the Firebase website to be displayed on the application. The application built can set a large amount of water and heat it to the desired temperature before sending it to Firebase and then to NodeMCU. The result of this research is an application that is able to control and monitor a water heater with an average measurement difference of 0.38 liters and an average error percentage of 7.11% The relay control system in the application has an average delay time of 3.6 seconds.